The mediating effect of technology adoption on participation, social capital, and empowerment in the agriculture sector of sri Lanka - Hassan, Mohammad Mujaheed; Wan Jaafar, Wan Munira; Ahmad, Nobaya; Herath, Muthubandage Mahinda (Fakulti Ekologi Manusia, Universiti Putra Malaysia, 2024)
The question of how to assist farmers in developing more sustainable empowerment remains a significant challenge. In order to fill in the gaps in the literature, this research examined how participation and social capital affect both technology adoption and empowerment. Additionally, the mediating role of agricultural technology adoption between determinants of empowerment and empowerment was examined for the first time. SPSS version 26 and PLS-SEM version 3.3 were used to analyse all direct and indirect associations between participation, social capital, technology adoption and empowerment. 322 Sri Lankan chilli farmers were interviewed using a multi-stage random sampling procedure. The findings accounted for 74.1% of the variation in empowerment. It was determined that the mediating function of agricultural technology adoption was important for all relationships between participation, social capital, and empowerment. In addition, participation and social capital were identified as favourable predictors of technology adoption and accounted for 51.2% of the variance in adoption. As a result, the findings of the current study are critical for filling gaps in the literature by improving understanding of the impact of empowerment factors on agricultural technology adoption and empowerment in the agriculture sector.